To the problem of formation the synergetic model of nonlinear personality - V. P. Kultenko (Ukrainian Cultural Studies, 2020)
The article investigates a potential of synergetics in the formation of modern nonlinear personality. Synergetics is seen in the quality of the methodology of psychophysiological, educational, social, communal and other problems of modernity. Psychosynergetics considers a person as an open hypersystem of synergetic order, which has a phase structure and is in an unbalanced state. The system in unbalanced conditions behaves fundamentally differently and requires means of self-preservation, self-adjustment. When people faced with new, atypical situations, they react to them atypically, and therefore urgently need to develop new psychological strategies that provide psychosynergetics. The modern world is a world of systemic crisis, which is observed in various spheres of life. Modern world is requires a systematic holistic thinking, unity of fundamental theoretical and practical applied knowledge and skills, creative approach and nonlinearity of thinking in solving problems. It is important for a person order to solve the conflict problems between the external and internal world, and establish mechanisms of nonlinear positive feedback with the external world. Internal consistency of system elements is also a necessary condition for success. The main task of the individual is to realize himself as a whole, as a system. The whole must figure itself out in order to fit harmoniously into the system of the world. Thus, the whole is acquires qualitatively new parameters and characteristics, according to which there is a change of its parts through the mechanisms of system coordination. The principles of holism require a person to develop special abilities and strategies (psycho-emotional, ideological), adequate to the nature and stage of the environment: flexibility of thinking, corresponding to its nonlinear characteristics, temporality – self-organization, systemic coherence. Education, which is also an element of a single system, must have its own and teach a person the skills to create and maintain integrity, be able to identify and relate themselves as a whole with the integrity of another person or society.